Use of comet assay for genotoxicity assessment in fishes from Gomti River - Nagpure, N S; Sharma, Shilpi; Pandey, Sanjay; Kumar, Ravindra; Srivastava, Satish K; Verma, M S; Kapoor, D (Indian Journal of Fisheries, 2011)
An increasing number of genotoxic chemicals are being released into the aquatic environment, posing serious damage to ourrich aquatic biodiversity and also indirectly to human health. In view of the above, attempts have been made to explore thefeasibility of application of comet assay for biomonitoring of fish from polluted sites of River Gomti in Lucknow (UttarPradesh), which has been exposed to heavy pollution during the recent years. For comet assay, blood samples of two fishspecies found in the river namelyLabeo rohita and Puntius puntius, were tested. Blood samples from fishes of the samespecies collected from the fish ponds of the National Bureau of Fish Genetic Resources (NBFGR), Lucknow were taken ascontrol for comparison. The samples were then subjected to comet assay for assessing DNA damage. Significant differenceswere observed with respect to the two important comet parametersviz., percentage tail DNA and tail length as compared tocontrol. The results indicated the sensitivity and suitability of comet assay for 'in situ' biomonitoring programmes to exploregenotoxicity of environmental pollutants.